1987
DOI: 10.1159/000275956
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Adrenergic Stimulation and Radiosensitivity on the Rat Submaxillary Gland

Abstract: The submaxillary glands were exposed to fractionated irradiation comparable to 50 Gy in clinical practice and a single fraction of 50 Gy. Half the number of rats were given cyclocytidine, an alpha-adrenergic agonist which depletes the serous cell granules before irradiation was embarked upon. Our results show that irradiation causes a significant, irreversible destruction of serous cells. With cyclocytidine pretreatment, the radiodamage was diminished and this drug is suggested to act as a radioprotector, depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…This increases the cell survival, as has previously been shown [1], One hour after injection of cyclocytidine there is an almost total depletion of secretory granules in the salivary gland serous cells. After 6 h a slight tendency of regranula tion is seen, with a few small granules apically located.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This increases the cell survival, as has previously been shown [1], One hour after injection of cyclocytidine there is an almost total depletion of secretory granules in the salivary gland serous cells. After 6 h a slight tendency of regranula tion is seen, with a few small granules apically located.…”
Section: Discussionsupporting
confidence: 75%
“…Dur ing this time the depletion of heavy-metal granules is a the most, and the morphological destruction would thus be diminished, as we have described in earlier publications [1,2], leading to a more preserved function of the salivary glands postirradiation therapy. In our experimental model we have found that one injection of cyclocytidine is sufficient to dcgranulate the serous cells.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…At that time, the focus of research was on prevention and treatment of salivary glands from post-radiotherapy functional loss applying sialogogues, radioprotective agents, and/or saliva substitutes. Regarding sialogogues, the observation that drug-induced depletion of submandibular serous cell granules before irradiation resulted in a decreased radiosensitivity of rodent submandibular glands linked the radiosensitivity of these cells to the content of secretory granules [4][5][6]. In rodents, these granules contain high amounts of proteolytic enzymes and transition metals [4].…”
Section: The 1989 Nih Consensusmentioning
confidence: 99%